Opportunistic QCT Bone Mineral Density Measurements Predicting Osteoporotic Fractures: A Use Case in a Prospective Clinical Cohort - Leonhardt, Yannik; May, Pauline; Gordijenko, Olga; Koeppen-Ursic, Veronika A.; Brandhorst, Henrike; Zimmer, Claus; Makowski, Marcus R.; Baum, Thomas; Kirschke, Jan S.; Gersing, Alexandra S.; Seifert-Klauss, Vanadin; Schwaiger, Benedikt J. (Frontiers in Endocrinology, 2020)
Purpose: To assess whether volumetric vertebral bone mineral density (BMD) measured with opportunistic quantitative computed tomography (QCT) (i.e., CT acquired for other reasons) can predict osteoporotic fracture occurrence in a prospective clinical cohort and how this performs in comparison to dual-energy X-ray absorptiometry (DXA) measurements. Methods: In the database of our fracture liaison service, 58 patients (73±11 years, 72% women) were identified that had at least one prevalent low-energy fracture and had undergone CT of the spine. BMD was determined by converting HU using scanner-specific conversion equations. Baseline DXA was available for 31 patients. During a 3-year follow-up, new fractures were diagnosed either by (i) recent in-house imaging or (ii) clinical follow-up with validated external reports. Associations were assessed using logistic regression models, and cut-off values were determined with ROC/Youden analyses. Results: Within 3 years, 20 of 58 patients presented new low-energy fractures (34%). Mean QCT BMD of patients with fractures was significantly lower (56±20 vs. 91±38 mg/cm3; p=0.003) and age was higher (77±10 vs. 71±11 years; p=0.037). QCT BMD was significantly associated with the occurrence of new fractures, and the OR for developing a new fracture during follow-up was 1.034 (95% CI, 1.010–1.058, p=0.005), suggesting 3% higher odds for every unit of BMD decrease (1mg/cm3). Age and sex showed no association. For the differentiation between patients with and without new fractures, ROC showed an AUC of 0.76 and a Youden’s Index of J=0.48, suggesting an optimal cut-off value of 82 mg/cm3. DXA T-scores showed no significant association with fracture occurrence in analogous regression models. Conclusion: In this use case, opportunistic BMD measurements attained through QCT predicted fractures during a 3-year follow-up. This suggests that opportunistic measurements are useful to reduce the diagnostic gap and evaluate the fracture risk in osteoporotic patients.